FROM TREND TO TRUTH : EDUKASI PEMILIHAN SKINCARE DAN KOSMETIK AMAN PADA GENERASI ALPHA DI SMA N 5 KENDARI - Fadhliyah Malik; Sahidin Sahidin; Astri Alawia; Hajah Ningsih Inta; Muhammad Rifky Wahyu Alfatih; Siti Suriyani Kapa; Wiwik Rusdin (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The increasing use of skincare and cosmetics among adolescents raises the risk of using unsafe products due to limited knowledge in selecting appropriate and legally approved items. This condition prompted the implementation of a community service program aimed at improving the knowledge and awareness of students at SMA Negeri 5 Kendari in choosing safe products according to their skin needs and identifying potentially harmful ones. The activity was conducted through educational outreach using interactive lectures, leaflet distribution, discussions, question-and-answer sessions, and evaluation through pretests and posttests. The materials included the influence of skincare trends on social media, how to choose safe and legal products, the importance of understanding skin types, and identifying characteristics of safe and harmful cosmetics. The results showed improved participant understanding, reflected in evaluation outcomes and active participation in discussions. Participants became more capable of distinguishing safe and risky products and more critical of cosmetic information. This activity effectively enhanced adolescents’ health literacy and encouraged more selective behavior in maintaining skin health